Crypto market relationships with bric countries' uncertainty: A wavelet-based approach - Almeida, J.; Gaio, C.; Gonçalves, T. C. (Technological Forecasting and Social Change, 2024)
This study focuses on exploring the relationships between different categories of crypto assets and measures of uncertainty in BRIC countries, specifically examining geopolitical risk (GPR) and economic policy uncertainty (EPU). Our findings indicate that the co-movement of the EPU and GPR indexes with different categories of crypto assets is influenced by factors such as the time period, investment horizons, and the type of event, and that it differs across crypto assets. An overall pattern is observed, suggesting that the crypto market does not act as a hedge against economic policy uncertainties (EPU) but demonstrates a hedging effect against geopolitical risk (GPR). This distinction in hedging effectiveness is influenced by the nature of events (COVID-19 and the Russian invasion of Ukraine), since investors' expectations and perception of risk differ during these events. Furthermore, our analysis shows that stablecoins and memecoins do not exhibit consistent results in relation to GPR and EPU, suggesting that they may not serve as reliable hedging instruments against geopolitical risks or economic policy uncertainties in the BRIC countries. Our findings carry important implications for investors, portfolio managers, policy makers, and researchers, offering insights into portfolio risk management, regulatory frameworks, and the behavior of the cryptocurrency market in the face of uncertainties.